Comparison of prognosis of separated and non‐separated tooth autotransplantation. (4th September 2012) - Yoshino, K.; Kariya, N.; Namura, D.; Noji, I.; Mitsuhashi, K.; Kimura, H.; Fukuda, A.; Kikukawa, I.; Hayashi, T.; Yamazaki, N.; Kimura, M.; Tsukiyama, K.; et al.
Summary The aim of this study was to compare the prognosis of separated and non‐separated tooth autotransplantation of the upper first and second molars with complete root formation undertaken at dental clinics. The participating dentists were requested to provide information on transplantations they had undertaken from 1 January 1990 to 31 December 2010. Data on a total of 708 teeth from 637 patients were collected. This study analysed 35 separated teeth and 22 non‐separated teeth of 47 participants ranging from 27 to 76 years of age (mean age: 55·0 years) after data screening and elimination. The cumulative post‐transplantation survival rate at 10 years was 77·1% for separated teeth and 63·6% for non‐separated teeth as calculated with the Kaplan–Meier method. There were no significant differences between separated teeth and non‐separated teeth in a log rank test (P = 0·687). Separated‐tooth autotransplantation can help fill narrow recipient sites and increase occlusal supporting zones, but the clinical success rate was only 48·6%. Although transplantation of teeth with complete root formation has limited prognosis, transplantation of upper first and second molars, whether separated or non‐separated, is a viable option to replace missing teeth.